2013
DOI: 10.13102/sociobiology.v60i4.446-452
|View full text |Cite
|
Sign up to set email alerts
|

Neotenic reproductives influence worker caste differentiation in the termite Reticulitermes speratus (Isoptera; Rhinotermitidae)

Abstract: Division of labor among castes in social insect colonies increases ergonomic efficiency and colony-level fitness, and has played a key role in the ecological success of social insects. Knowledge of the factors that regulate castes is important for understanding adaptive social organization. Our previous study on the termite Reticulitermes speratus demonstrated that the presence of a pair of nymphoid reproductives during development affected offspring caste ratios. In the present study, we investigated further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…There are three types of reproductives in a termite colony: the primary, secondary and tertiary reproductives. Recently, Hayashi et al (2013) found that the termite colony Reticulitermes speratus that lost the primary reproductive castes will form the secondary reproductive castes (neotenic reproductive) within four to seven days. In the colony there is a main colony, where the main queen lives and satellite units, in which secondary reproductive are laying eggs.…”
Section: Subterranean Termite Colonymentioning
confidence: 99%
“…There are three types of reproductives in a termite colony: the primary, secondary and tertiary reproductives. Recently, Hayashi et al (2013) found that the termite colony Reticulitermes speratus that lost the primary reproductive castes will form the secondary reproductive castes (neotenic reproductive) within four to seven days. In the colony there is a main colony, where the main queen lives and satellite units, in which secondary reproductive are laying eggs.…”
Section: Subterranean Termite Colonymentioning
confidence: 99%
“…The differentiation of neotenic reproductives is controlled by genetic, maternal, and environmental factors. In Reticulitermes speratus and several other species, for instance, genetic, and maternal factors influenced by sex-linked genetic mechanisms, i.e., the asexual queen succession (AQS) system, are responsible for the neotenic differentiation (Hayashi et al, 2007;Matsuura et al, 2009;Matsuura et al, 2018;Hellemans et al, 2019), although environmental factors during the postembryonic development also affect the caste fate determination (Hayashi et al, 2007(Hayashi et al, , 2013. In contrast, environmental factors during postembryonic development, such as social interactions between reproductives and nonreproductive castes, are also determinant force for the neotenic differentiation (Lüscher, 1974;Shimoji et al, 2017;Sun et al, 2017;Masuoka et al, 2021).…”
mentioning
confidence: 99%